A Rare Case of Eosinophilic Ileitis and the Role of Motorized Spiral Enteroscopy in Its Diagnosis - Isabel Tarrio; Marta Moreira; Tarcísio Araújo; Emília Guerreiro; Carmélia Rodrigues; Luís Lopes (GE: Portuguese Journal of Gastroenterology, 2022)
Introduction: Eosinophilic gastrointestinal disorders are rare idiopathic conditions characterized by eosinophilic infiltration of any area of the gastrointestinal tract. The clinical presentation is variable and depends on the location and depth of the eosinophilia. Peripheral eosinophilia or elevated serum IgE levels may be present and histological analysis is necessary to a definite diagnosis. Presentation: A 40-year-old male presented with generalized abdominal pain, nausea, vomiting, diarrhea and anorexia for 1 month and unintended weight loss for 2 months. He had anemia, peripheral eosinophilia, slight hypokalemia, an elevated fecal calprotectin and “a thin sheet of bilateral pleural effusion, reduced-volume ascites and parietal thickening of the entire ileum” in the thoracoabdominal CT scan. An elevated serum IgE was absent and stool for parasites or bacteria, viral serologies, mycobacteria direct exam and culture, and celiac disease screening were negative. The endoscopic exams showed no significant alterations; random ileal biopsies were collected by antegrade motorized spiral enteroscopy and revealed a very fragmented mucosa with inflammatory infiltrate with about 35 eosinophils per high-power field and an altered eosinophil distribution in the ileal wall. The patient initiated oral prednisolone for eosinophilic ileitis, with clinical, analytical, and imagiological improvement. Conclusion: Eosinophilic ileitis is a rare condition but should be considered in the differential diagnosis of unexplained gastrointestinal symptoms and ascites, particularly in the presence of peripheral eosinophilia. Motorized spiral enteroscopy can be helpful in the diagnosis, allowing the collection of biopsy specimens effectively and safely.